Design of Piperazine Organoiron Macromolecules with Antibacterial and Anticancer Activity. Issue 8 (4th February 2016) - Abd‐El‐Aziz, Alaa S.; Abdelghani, Amani A.; Pearson, Jason K.; Awad, Mohamed K.; Overy, David P.; Kerr, Russell G.
Abstract : A series of organoiron complexes containing piperazine units have been synthesized via sequential nucleophilic aromatic substitutions. The structures and molecular properties of these complexes are investigated using various spectroscopic and analytical techniques. Cyclic voltammetric studies are conducted at various temperatures and the electrochemical analyses for the iron‐containing macromolecules show broadening of the cathodic peak at a higher molecular weight linear chain. The molecular structures of the series of complexes are investigated using Merck molecular force field. All conformers show similar energies and a flexible structure. Scanning electron microscopy is also used to examine the surface morphology. Some of these complexes exhibit activity toward Gram‐positive bacteria (Methicillin‐resistant Staphylococcus aureus and Staphylococcus warneri ), as well as MCF7 and HTB26 breast cancer cell lines. Abstract : Piperazine–organoiron macromolecules are prepared. These macromolecules exhibit good thermal stability as well as antibacterial and anticancer activity. The Merck molecular force field is used for molecular mechanics modeling of the series of complexes and all conformers show similar energies and flexible structures.